Development and application of a geospatial wildfire exposure and risk calculation tool. (January 2015) - Thompson, Matthew P.; Haas, Jessica R.; Gilbertson-Day, Julie W.; Scott, Joe H.; Langowski, Paul; Bowne, Elise; Calkin, David E.
Abstract: Applying wildfire risk assessment models can inform investments in loss mitigation and landscape restoration, and can be used to monitor spatiotemporal trends in risk. Assessing wildfire risk entails the integration of fire modeling outputs, maps of highly valued resources and assets (HVRAs), characterization of fire effects, and articulation of relative importance across HVRAs. Quantifying and geo-processing wildfire risk can be a complex and time-intensive task, often requiring expertise in geospatial analysis. Researchers and land managers alike would benefit from a standardized and streamlined ability to estimate wildfire risk. In this paper we present the development and application of a geospatial wildfire risk calculation tool, FireNVC. We describe the major components of the tool and how they align with a geospatial wildfire risk assessment framework, detail a recent application of the tool to inform federal wildfire management and planning, and offer suggestions for future improvements and uses of the tool. Highlights: We review the development of FireNVC, a geospatial wildfire risk calculation tool. FireNVC is a flexible platform to assess risk to multiple resources and assets. FireNVC enables a streamlined process for quantifying risks at landscape scales. We apply the tool to help prioritize risk mitigation planning on federal land. Sensitivity analysis suggests results are robust for prioritization.